Pengaruh Kemiskinan terhadap Tindak Kriminalitas di Kota Bekasi - Bunga Chantiqa; Hanifa Putri Wardhani; Raisah Zettira Hermawan; Siska Amalia; Wanda Sari Tambang; Mic Finanto Ario Bangun (Concept: Journal of Social Humanities and Education, 2024)
Investigating how poverty affects crime rates in Bekasi City is the main objective of this study. The approach takes a literature review approach, synthesizing research from databases like Google Scholar and Mendeley. Even in the contemporary day, many people in Bekasi City still live in poverty, which puts them in a position where they may resort to crime as a means of subsistence. Crime rates are positively correlated with poverty levels, suggesting that economic and income disparity is a motivating factor for criminal behavior. This study sheds light on the relationship between poverty and criminal behavior, and it supports initiatives to alleviate poverty as a means of lowering crime rates.